Spin gapped metals: A novel class of materials for multifunctional spintronic devices - Sasioglu, E.; Tas, M.; Ghosh, S.; Beida, W.; Sanyal, B.; Blugel, S.; Mertig, I. (Elsevier, 2025)
Gapped metals, a recently proposed class of materials, possess a band gap slightly above or below the Fermi level, behaving as intrinsic p- or n-type semiconductors without requiring external doping. Inspired by this concept, we propose a novel material class: spin gapped metals. These materials exhibit intrinsic p- or ntype character independently for each spin channel, similar to dilute magnetic semiconductors but without the need for transition metal doping. A key advantage of spin gapped metals lies in the absence of band tails that exist within the band gap of conventional p- and n-type semiconductors. Band tails degrade the performance of devices like tunnel field-effect transistors (causing high subthreshold slopes) and negative differential resistance tunnel diodes (resulting in low peak-to-valley current ratios). Here, we demonstrate the viability of spin gapped metals using first-principles electronic band structure calculations on half-Heusler compounds. Our analysis reveals compounds displaying both gapped metal and spin gapped metal behavior, paving the way for next-generation multifunctional devices in spintronics and nanoelectronics.
Keywords: Heusler compounds; Ab-initio calculations; Density functional theory calculations; Gapped metals; Magnetic materials